Assessing the value of ecological intensification in improving smallholder farmers' food security and rural livelihoods in a changing climate - Rusere, Farirai (Department of Environmental and Geographical Science, 2023)
Attaining the twin goals of food security and environmental sustainability has spurred focus on two main models of production, sustainable and ecological intensification as means to produce more food per unit land area while simultaneously ensuring environmental sustainability. A better understanding of their suitability and applicability in diverse and heterogeneous biophysical and socio-economic situations of smallholder farmers is still largely needed in sub Saharan Africa (SSA). This study aimed to assess the value of ecological intensification of agriculture to improve food production systems and environmental sustainability in smallholder farming systems in the face of climate variability and change. This study uses two rural districts in South Africa namely Vhembe and Amathole from Limpopo and the Eastern Cape provinces respectively as a case study to explore how ecological intensification can help smallholder farmers. The study explored the fit and potential of ecological intensification in smallholder agricultural systems and steps to be taken to support its implementation and development. The study then uses the Design, Explain, Evaluate and Design (DEED) approach to develops pathways relying on ecological intensification technologies and suiting different farm types of smallholder agriculture. Two iterations of the DEED approach were performed that enabled characterisation of farmers and farming systems and farming systems analysis of challenges and constraints that helped to identify and link specific ecosystem services with suitable ecological intensification options. Furthermore, the study assesses the acceptance and use of ecological intensification options in the heterogeneous biophysical and socioeconomic context of smallholder farmers through the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. Besides the productivity potential, the study sheds light on locally relevant knowledge that must be considered to enable acceptance and use of ecological intensification options. I finally explored the potential of ecological intensification to meet the goals of improving productivity and environmental sustainability concurrently through a biophysical modelling approach encompassing a farm typology, a crop model and a farm focussed greenhouse gas calculator. The results provide valuable insights into the ongoing debate on how to intensify smallholder cropping systems. More specifically, the results show that the integration of agroecological approaches in smallholder cropping systems has the potential to deliver ecological intensification in which productivity is improved and ecosystem services such as climate change regulation through reduction of GHG emissions from cropping systems are simultaneously increased to enhance environmental sustainability. Overall, the study articulates various pieces of evidence to show that ecological intensification is suitable, applicable and, can attain the twin objectives of improving food production systems concurrently ensuring environmental sustainability, in heterogeneous smallholder agricultural systems in SSA. This contribution raises the need for further attention to be given to smallholder agricultural intensification policies and research or to agricultural intensification to explicitly consider the heterogeneous biophysical and socioeconomic circumstances of smallholder farmers in SSA.